2014
DOI: 10.1021/ma501330v
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Conjugated Polycarbazole with High Porosity via Structure Tuning

Abstract: Monomer building units play a key role in the porosity and adsorption performance of porous conjugated polymers. Three tetracarbazolyl-substituted monomers (Cz-8–10) with similar molecular structures were designed and prepared in order to tune the porosity and pore size distribution of the obtained porous conjugated polycarbazoles (CPOP-8–10) via FeCl3-promoted carbazole-based oxidative coupling polymerization. Polymers CPOP-8 and CPOP-10 exhibit microporous nature similar to most of reported conjugated microp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
78
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(80 citation statements)
references
References 35 publications
2
78
0
Order By: Relevance
“…This may be attributed to the combination of the improved micropore volume (up to 0.68 cm 3 g -1 ) and the hierarchically porous structure, which 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 makes that ultramicropores more efficient for the kinetic CO 2 molecules in the adsorption process. Notably, at 273 K and 1 bar, MOP-8C presents a high CO 2 uptake up to 214 mg g -1 , which surpasses most of the known porous organic polymers and the porous carbon materials, such as CPOPs (182 mg g -1 ), [45][46] HCPs (181 mg g -1 ), [47][48] CTFs (143 mg g -1 ), 49 CMPs (122 mg g -1 ), 50 nitrogen-doped graphene (114 mg g -1 ), 51 HPNCs (207 mg g -1 ). 52 Moreover, this value could also be comparable with those of the porous carbon materials with high pore volume and nitrogen content, for example microporous carbon TPC-1 (216 mg g -1 ) 53 with a pore volume of 1.23 cm 3 g -1 and a nitrogen content of 20.87 wt%, and mesoporous carbon OMC (132 mg g -1 at 278K) 54 with a pore volume of 2.17 cm 3 g -1 .…”
Section: Resultsmentioning
confidence: 98%
“…This may be attributed to the combination of the improved micropore volume (up to 0.68 cm 3 g -1 ) and the hierarchically porous structure, which 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 makes that ultramicropores more efficient for the kinetic CO 2 molecules in the adsorption process. Notably, at 273 K and 1 bar, MOP-8C presents a high CO 2 uptake up to 214 mg g -1 , which surpasses most of the known porous organic polymers and the porous carbon materials, such as CPOPs (182 mg g -1 ), [45][46] HCPs (181 mg g -1 ), [47][48] CTFs (143 mg g -1 ), 49 CMPs (122 mg g -1 ), 50 nitrogen-doped graphene (114 mg g -1 ), 51 HPNCs (207 mg g -1 ). 52 Moreover, this value could also be comparable with those of the porous carbon materials with high pore volume and nitrogen content, for example microporous carbon TPC-1 (216 mg g -1 ) 53 with a pore volume of 1.23 cm 3 g -1 and a nitrogen content of 20.87 wt%, and mesoporous carbon OMC (132 mg g -1 at 278K) 54 with a pore volume of 2.17 cm 3 g -1 .…”
Section: Resultsmentioning
confidence: 98%
“…These results demonstrated that such carbazole‐functionalized MOPs have great potential to increase the gas capture capacity. It has been showed that the porous properties of CMPs mainly depend on the length of the rigid connecting strut and topological structure design . However, until now the carbazole‐based CMPs with soft connecting chain have been never investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] These materials, with their pore size approaching molecular dimensions, have the potential to be used for molecular storage and separation, [6][7][8][9][10][11] catalysts or catalyst supports, [12][13][14][15][16][17][18] and sensors. [21][22][23][24][25][26][27] One of the main issues concerning the porous network of covalently bonded building blocks (referred to as a "covalent network") is to fabricate a hierarchical pore structure, i.e., a network consisting of interconnected pores of different sizes. [21][22][23][24][25][26][27] One of the main issues concerning the porous network of covalently bonded building blocks (referred to as a "covalent network") is to fabricate a hierarchical pore structure, i.e., a network consisting of interconnected pores of different sizes.…”
Section: Introductionmentioning
confidence: 99%